High Temperature, pH, and Hypoxia Cause Oxidative Stress and Impair the Spermatic Performance of the Amazon Fish Colossoma macropomum - Castro, Jonatas S.; Braz-Mota, Susana; Campos, Derek F.; Souza, Samara S.; Val, Adalberto L. (Frontiers in Physiology, 2020)
The control of abiotic parameters is fundamental for fish survival, growth and reproduction. These factors have a direct effect on sperm quality. Thus, this study evaluated the effect of different temperatures (29, 31, 33 and 35 ° C), pHs (4 and 8) and hypoxia (1 mgO2 L-1) on sperm motility of Colossoma macropomum (tambaqui). The results indicated a longer duration of sperm motility at 29 °C (50.1 ± 2.70 s) that progressively decreased when exposed to 35 °C (31.2 ± 1.31 s) and hypoxia at pH 4 (27.4 ± 1.42 s) and 8 (30.44 ± 1.66 s) (p <0.05), respectively. Sperm oxygen consumption increased in hypoxia at both pH (pH 4= 61.22; pH 8= 54.74 pmol∙s-1). There was an increase in the activity of glutathione-S-transferase (GST) and superoxide dismutase (SOD), as well as in lipid peroxidation levels (LPO) and DNA damage in sperm exposed to higher temperatures and hypoxia. The pH 4 and pH 8 under normoxia did not affect the quality of C. macropomum sperm. These results suggest that water warming and acidification, consequences of climate changes, significantly affect the reproduction of C. macropomum, reducing the quality of spermatozoids during fertilization.